Evaluation of coagulation during treatment with directly acting antivirals in patients with hepatitis C virus related cirrhosis. (23rd February 2017) - Tripodi, Armando; D'Ambrosio, Roberta; Padovan, Lidia; Tosetti, Giulia; Aghemo, Alessio; Primignani, Massimo; Chantarangkul, Veena; Peyvandi, Flora; Colombo, Massimo
Abstract: Background & Aims: The effect of direct‐acting‐antivirals (DAA) on coagulation of hepatitis‐C‐virus (HCV)‐related cirrhosis is unknown. Methods: We investigated 28 patients on DAA treatment and performed prothrombin‐time, thrombin generation with and without thrombomodulin, whole‐blood thromboelastometry, as well as the individual procoagulants (II, VIII, XIII, von Willebrand) and anticoagulants, antithrombin and protein‐C. Results: Patients had undetectable HCV‐RNA at the end‐of‐ treatment and at 12‐weeks after end‐of‐treatment (sustained virological response). Transaminases were significantly decreased at both end‐of‐treatment and at 12‐weeks. Prothrombin‐time declined at 12‐weeks, but did not reach statistical significance. Factor‐II, protein‐C and antithrombin increased significantly at end‐of‐treatment ( P <.001) and persisted at 12‐weeks. Factor‐VIII decreased at end‐of‐treatment and to a greater extent at 12‐weeks when reached statistical significance ( P <.05). Factor‐VIII/protein‐C ratio decreased sharply, reached statistical significance at end‐of‐treatment ( P <.01) and persisted at 12‐weeks. Von‐Willebrand decreased at end‐of‐treatment and reached statistical significance at 12‐weeks ( P <.001). Endogenous‐thrombin‐potential without thrombomodulin increased significantly at end‐of‐treatment ( P <.01) and persisted at 12‐weeks. No changes were observed after addition of thrombomodulin. Endogenous‐thrombin‐potential ratio (with/without thrombomodulin) decreased and reached statistical significance at 12‐weeks ( P <.05). Thromboelastometry clotting time decreased sharply, reached statistical significance at end‐of treatment ( P <.001) and persisted at 12‐weeks. Conclusions: Treatment with DAAs in HCV‐related cirrhosis results in improvement of the individual pro‐ and anticoagulants. It can be hypothesised that the net effect does not substantially modify their balance (as shown by the unchanged thrombin generation in the presence of thrombomodulin) but makes it more stable and less amenable to be perturbed as presumably occurs before treatment when there is a partial deficiency for both.